Efficient Generation of Viral and Integration‐Free Human Induced Pluripotent Stem Cell‐Derived Oligodendrocytes. (17th August 2016) - Espinosa‐Jeffrey, Araceli; Blanchi, Bruno; Biancotti, Juan Carlos; Kumar, Shalini; Hirose, Megumi; Mandefro, Berhan; Talavera‐Adame, Dodanim; Benvenisty, Nissim; de Vellis, Jean
Abstract: Here we document three highly reproducible protocols: (1) a culture system for the derivation of human oligodendrocytes (OLs) from human induced pluripotent stem cells (hiPS) and their further maturation—our protocol generates viral‐ and integration‐free OLs that efficiently commit and move forward in the OL lineage, recapitulating all the steps known to occur during in vivo development; (2) a method for the isolation, propagation and maintenance of neural stem cells (NSCs); and (3) a protocol for the production, isolation, and maintenance of OLs from perinatal rodent and human brain‐derived NSCs. Our unique culture systems rely on a series of chemically defined media, specifically designed and carefully characterized for each developmental stage of OL as they advance from OL progenitors to mature, myelinating cells. We are confident that these protocols bring our field a step closer to efficient autologous cell replacement therapies and disease modeling. © 2016 by John Wiley & Sons, Inc.